PROTOTYPE OF A DESKTOP-BASED COMMUNICATION APPLICATION USING A DELAY TOLERANT NETWORK ARCHITECTURE - Slameta; Ashari; Muh Haikal Pandia Situmorang; Kamal Falah Firdaus; Griffani Megiyanto R (Jurnal Teknologi Informasi Universitas Lambung Mangkurat (JTIULM), 2022)
Currently, the process of exchanging information or data is carried out quickly, precisely, effectively and efficiently using the internet network. However, in reality, there are still some problems in areas that are difficult to get a signal, such as connection loss or unstable connection. One of the proposed solutions to anticipate this problem is the implementation of a network using the Delay Tolerant Network architecture. This architecture was chosen because of its basic capability, namely being able to send files even in a high delay state or used in areas with intermittent properties. The implementation carried out is making a chat application prototype that is able to function in intermittent areas and can be used for communication between sender and receiver in difficult signal conditions. The hardware used is a raspberry pi and supporting software using ION-DTN and traffic management designed using the python programming language. The application is tested by applying the concept of functionality testing, namely with full signal condition scenarios and limited signal conditions as a representation of the intermittent area. The test results show that the application is able to function based on the initial design with a delay with test variations of 1-10 minutes of signal dropout time. Further development can be done by adding a chat feature so that it is able to send more varied data.